Peran Posyandu untuk Pemantauan Tumbuh Kembang Anak di Kelurahan Kenangan Baru - Intan Suwandi; Salman Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to enhance the role of integrated health service posts (Posyandu) in monitoring child growth and development in Kenangan Baru Village, so that children in Kenangan Baru Village can grow and develop optimally. The research method used in this study was participatory action research (PAR) with a qualitative approach. This research was conducted in several stages: preparation, intervention, and evaluation. Through this community service program, it is hoped that it will make a significant contribution to improving the knowledge and skills of Posyandu cadres in monitoring child growth and development, as well as increasing parental awareness and participation in monitoring child growth and development at the Posyandu in Kenangan Baru Village. This activity also helps build community independence by increasing public awareness and participation in development activities. The Community Service Program (KKN) in Kenangan Baru Village was successfully implemented and had a positive impact on the community. Through coordination and introductions with the village office staff and Posyandu cadres, we were able to understand the existing conditions and design an appropriate work program.